2015
DOI: 10.1002/pssa.201532309
|View full text |Cite
|
Sign up to set email alerts
|

Study of precursor chemistry and solvent systems in pp-MOCVD processing with alumina case study

Abstract: Alumina synthesis presents an opportunity to study the processing science of direct liquid injection pulsed‐pressure MOCVD. The current study uses three alumina precursors and two solvent systems to study the physical chemistry of the flash evaporation processes that can occur in the pulsed‐pressure approach from fundamental considerations and experimental observation. Three precursors were studied, aluminum tri‐isopropoxide, aluminum tri‐secbutoxide, and aluminum tri‐tertbutoxide, with hexane and toluene solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Hexane has six times higher vapor pressure than toluene, so one might conclude that hexane would be a vastly superior choice. However in our recently reported preliminary study of pp‐MOCVD alumina deposition using different precursors and solvents, we did not get markedly different results due to solvent alone . The erroneous shorter drop life for toluene seemed to possibly fit with one aspect of our previous results, but this could definitely be due to one of many other factors like solvent and precursor chemistry and variability of working conditions.…”
supporting
confidence: 39%
“…Hexane has six times higher vapor pressure than toluene, so one might conclude that hexane would be a vastly superior choice. However in our recently reported preliminary study of pp‐MOCVD alumina deposition using different precursors and solvents, we did not get markedly different results due to solvent alone . The erroneous shorter drop life for toluene seemed to possibly fit with one aspect of our previous results, but this could definitely be due to one of many other factors like solvent and precursor chemistry and variability of working conditions.…”
supporting
confidence: 39%
“…Hexane is a much more volatile solvent than toluene, with P sat = 21819 Pa for hexane compared to P sat = 4171 Pa for toluene at 300K, but the high evaporation enthalpy of hexane leads to a strong cooling of droplets. The vaporization efficiency seems to be much lower for hexane than for toluene . Previous studies with toluene and TTIP have also demonstrated that very high vaporization efficiency is possible …”
Section: Optimal Process Parameters and Controlmentioning
confidence: 84%
“…The alumina precursor (2 g) was dissolved in cyclohexane (80 ml) to form a final concentration of 0.02 M. Cyclohexane was selected as a solvent since there are studies where it has been observed that it favors the growth of spherical structures with few agglomerations (Gunby, Krumdieck, Murthy, Masters, & Miya, 2015).…”
Section: Precursor and Solventmentioning
confidence: 99%